Drug-Resistant Epilepsy: Multiple Hypotheses, Few Answers - Tang, Fei; Hartz, Anika M. S.; Bauer, Björn (Frontiers in Neurology, 2017)
Epilepsy is a common neurological disorder that affects over 70 million people worldwide. Despite the recent introduction of new antiseizure drugs (ASDs), about one third of patients with epilepsy have seizures refractory to pharmacotherapy. Early identification of patients who will become refractory to ASDs could help direct such patients to appropriate nonpharmacologic treatment, but the complexity in the temporal patterns of epilepsy could make such identification difficult. The target hypothesis and transporter hypothesis are the most cited theories trying to ex-plain refractory epilepsy, but neither theory alone fully explains the neurobiological basis of pharmacoresistance. This review summarizes evidence for and against several major theories, in-cluding the pharmacokinetic hypothesis, neural network hypothesis, intrinsic severity hypothesis, gene variant hypothesis, target hypothesis, and transporter hypothesis. The discussion is mainly focused on the transporter hypothesis, where clinical and experimental data are discussed on mul-tidrug transporter overexpression, substrate profiles of ASDs, mechanism of transporter upregula-tion, polymorphisms of transporters, and the use of transporter inhibitors. Finally, future perspec-tives are presented for the improvement of current hypotheses and the development of treatment strategies as guided by the current understanding of refractory epilepsy.